Early stage primary gastric diffuse large B-cell lymphoma in a young HIV-positive patient - Guilherme Harada; Aloisio Felipe-Silva; José Guilherme Nogueira da Silva (University of São Paulo, 2014)
HIV infection is known to be associated with the development of a wide range of neoplasia. About 25 to 40% of HIV-positive patients will present some kind of malignancy in the course of the disease; among them 10% are non-Hodgkin lymphomas (NHL) and 20% of these are represented by the diffuse large B-cell lymphoma. HIV-positive patients have a relative risk of 110 times higher to develop neoplasia, than the non-infected population. The gastrointestinal (GI) tract is the most frequent extranodal site of involvement. However, the primary GI lymphoma is rare. The authors present a case of a 31-year-old male patient with a 16-year history of HIV infection, who deliberately withdrew the Highly Active Antiretroviral Therapy (HAART) regimen and was hospitalized because of a respiratory infection. Because of a long-term complaint of dyspepsia, an upper gastrointestinal endoscopy was performed disclosing a large elevated and ulcerated gastric lesion, which biopsy revealed a diffuse large B-cell lymphoma. Clinical, imaging and laboratory tests showed an early stage diagnosis: Lugano stage I. Although not frequent, the authors alert to considering this neoplasia in all HIV-positive patients with dyspeptic symptoms.